Towards societal impact through open research - Oefelein, Timon (Septentrio Conference Series, 2020)
See RECORDING. The United Nation’s 17 Sustainable Development Goals (SDGs) are now more relevant than ever because they express the relevancy of research to addressing urgent global needs. Thus we ask: How much scholarly content relates to these SDGs and what are the trends? How much of it successfully reaches its target audience, including policy makers and practitioners, and does Open Access (OA) publication make a difference? Finally, what best practices can be recommended to researchers to optimize the societal impact of their research? In order to find answers to these important and pressing questions, Springer Nature has partnered with The Association of Universities in the Netherlands (VSNU) to form a unique interdisciplinary impact working group that draws on Open Science practices. This presentation introduces the project group, describing its aims, and key interim results. This includes a summary of how the team built one of the world’s first SDG content classifiers using both machine learning and extensive human input from a team of subject experts. The SDG classifier is freely available online. Further, we’ll share key results from two large global researcher surveys. The first set of results outlines researchers’ motivations towards SDG research and its impact as evidenced by responses from some 9000 participants across the world. The second set of survey data, featuring 5900 responses, provides insight into usage trends of both OA and non-OA content. Together, our results provide unique and evidence-based insight into the volume and nature of SDG content, the role of open access in maximising reach and dissemination, and finally, how libraries can help researchers optimize societal impact. The presentation will be of interest to a wide audience, including members of the research assessment community and research offices; funders of SDG content; and academic support libraries supporting researchers with publication and impact.